A review of emerging adsorbents and current demand for defluoridation of water: Bright future in water sustainability. (February 2018) - Yadav, Krishna Kumar; Gupta, Neha; Kumar, Vinit; Khan, Shakeel Ahmad; Kumar, Amit
Abstract: Fluoride contamination of groundwater is a serious problem in several countries of the world because of the intake of excessive fluoride caused by the drinking of the contaminated groundwater. Geological and anthropogenic factors are responsible for the contamination of groundwater with fluoride. Excess amounts of fluoride in potable water may cause irreversible demineralisation of bone and tooth tissues, a condition called fluorosis, and long-term damage to the brain, liver, thyroid, and kidney. There has long been a need for fluoride removal from potable water to make it safe for human use. From among several defluoridation technologies, adsorption is the technology most commonly used due to its cost-effectiveness, ease of operation, and simple physical process. In this paper, the adsorption capacities and fluoride removal efficiencies of different types of adsorbents are compiled from relevant published data available in the literature and represented graphically. The most promising adsorbents tested so far from each category of adsorbents are also highlighted. There is still a need to discover the actual feasibility of usage of adsorbents in the field on a commercial scale and to define the reusability of adsorbents to reduce cost and the waste produced from the adsorption process. The present paper reviews the currently available methods and emerging approaches for defluoridation of water. Highlights: Adsorption capacities and fluoride removal efficiencies have been presented for a wide range of adsorbents. Aluminium-based adsorbents are most effective but it's leaching cause health problems. Langmuir isotherm and pseudo-second-order kinetic were found to be best fitting model. Current desorption strategies are inadequate and environmentally not sustainable. Reusability of an adsorbent is very important to make it sustainable. More integrated and economically viable adsorption techniques now needed.